Pengaruh Media Sosial Terhadap Keputusan Pembelian pada Usaha Fashion di Kota Jambi - Rajev Akbar Ratu; Deka Veronica; Endah Tri Kurniasih (Teewan Journal Solutions, 2026)
This study aims to analyze the influence of social media on consumer purchasing decisions in the fashion businessin Jambi City. Social media has become one of the primary platforms in marketing strategies, especially in thefashion industry, which heavily relies on visuals and trends. This research employed a quantitative approach usinga questionnaire distributed to 97 respondents who are consumers of fashion products in Jambi City. The collecteddata were analyzed using simple linear regression to determine the extent of social media's influence on purchasingdecisions. The results show that social media has a positive and significant effect on purchasing decisions. Thisstudy is expected to serve as a reference for fashion entrepreneurs in designing more targeted digital marketingstrategies.